IMPLEMENTASI KEBIJAKAN MAL PELAYANAN PUBLIK DI KABUPATEN NGANJUK - Siti Mudhawamah Siti Mudhawamah; Bambang Santoso Haryono Bambang Santoso Haryono; Alfi Haris Wanto Alfi Haris Wanto (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2022)
This research aims to explain the Implementation of the Public Service Mall Policy in the Regent’s Regulation No 17 of 2019 concering to Implementation of the Nganjuk Regency Public Service Mall which was analyzed using George Edwars III’s policy implementation theory and the theory of Public Service Standards based on Law No. 25 of 2009 concering to Public Service. The results showed that the implementation of the Nganjuk Public Service Mall policy was still not optimal. This is evidenced by the attitude of implementing policies that have not resumed operation at the Nganjuk Public Service Mall after the Covid-19 pandemic. Then the policy communication process has not been carried out optimally, so that the information received by the public is not evenly distributed. On the other hand, the successful implementation of the Nganjuk Public Service Mall policy can be seen in terms of resources, including human resources, and the facilities.